Knowledge, attitude and practice regarding motorcycle helmet usage among secondary school students in Kuantan, Malaysia - Mohamed Ariffin, Suzilawati; Setapani, Mimi Nor Aliza (National Institute of Occupational Safety and Health (NIOSH), Ministry of Human Resources Malaysia, 2018)
Malaysia has the highest road fatality risk (per 100,000 populations) compared to other ASEAN nations and more than 50% of the road accident fatalities involving motorcyclists. Hence, this becomes the leading cause of death among young people, aged 15–29 years. The most common cause of fatalities involving motorcyclist is the head injury., This present study aimed to evaluate the knowledge, attitude, and practice on helmet usage among secondary school students in Kuantan. A descriptive cross-sectional design (two months of data collection) was used in this study. Questionnaires were distributed to 200 participants from two schools in Kuantan. The main finding of this study suggests that common reason for the participants to wear a helmet is that ‘it can save a life’. Besides that, the poor practice regarding helmet usage was also found as only 4.5% of them wore the helmet all the time. However, the overall result showed that most of the participants have a good knowledge and positive attitude regarding utilization of helm